‘Nechto eroticheskoe’, ‘courir après l'ombre’? – logistical imperatives and the fall of Tashkent, 1859–1865 - Morrison, A (Taylor and Francis (Routledge), 2014)
This article explores the debates that preceded the Russian conquest of Tashkent in 1865. It argues that none of the explanations usually given for this – the ‘men on the spot’, ‘cotton hunger’, or the Great Game with Britain – is satisfactory. Instead, it shows that the War Ministry and the governors of Orenburg had advocated the capture of Tashkent from the late 1850s, and that General Cherniaev's assault in 1865 was at least tacitly authorized. The motives for the Russian advance combined the need for better supply chains to the steppe fortresses, a desire to ‘anchor’ their new frontier in a region with a sedentary population, and concern for security from attacks by the Khoqand Khanate. Economic considerations and rivalry with Britain played very minor roles.